USING RESEARCH ON MOTHER TONGUE ACQUISITION IN LANGUAGE EDUCATION - Berdieva Nilufar Ibadilullayevna (Sciental Journals Publishing, 2025)
This article analyzes scientific research conducted on mother tongue acquisition and highlights its practical application in language education. Research findings show that a strong foundation in native grammar and vocabulary serves as a key support in acquiring a foreign language. The article emphasizes the effectiveness of contrastive approaches, translation-based exercises, and understanding of cultural context as pedagogical tools. Native language-based methods create psychological comfort for learners and foster linguistic cognition. The study underscores the importance of integrating the methodological and didactic potential of the mother tongue into foreign language education.
Keywords: Mother tongue, modern language, language education, contrastive analysis, translation, methodology, linguistic thinking